Strategy For Developing The Kalimah Cave Tourist Attraction To Boost The Local Economy In Galing District - Reo Zaputra (SOUTHEAST ASIA JOURNAL oF GRADUATE OF ISLAMIC BUSINESS AND ECONOMICS, 2025)
This study aims to identify the tourism potential of Kalimah Cave in Galing District and formulate management strategies through the 4A approach (Attraction, Accessibility, Amenity, and Ancillary Services). The research method used is a qualitative approach with data collection techniques through interviews, observation, and documentation. Data analysis was conducted descriptively, supported by data validation through triangulation and member checking to enhance the credibility of the findings. The results of the study indicate that Goa Kalimah possesses unique historical attractions, marked by the presence of Arabic-like inscriptions on the cave entrance and the captivating natural panorama of Bukit Seburuan. However, there is a need for more varied attractions, improved accessibility, and the provision of supporting facilities such as parking areas and toilets to enhance visitor comfort. Additionally, the development of local businesses and tour guide services has the potential to positively impact the local economy. This study concludes that the implementation of a 4A-based management strategy can optimize the sustainable tourism potential of Goa Kalimah while promoting local economic growth